Proton Temperature Anisotropies in the Venus Plasma Environment During Solar Minimum and Maximum. Issue 1 (6th January 2022) - Rojas Mata, Sebastián; Stenberg Wieser, Gabriella; Futaana, Yoshifumi; Bader, Alexander; Persson, Moa; Fedorov, Andrey; Zhang, Tielong
Abstract: The proton population in Venus' plasma environment is characterized during periods of solar minimum and maximum using data from a particle mass‐energy spectrometer. Such characterizations at different levels of solar activity provides physical insight into solar‐cycle‐dependent plasma phenomena around the planet, for example mirror modes in the magnetosheath. Statistical distributions of proton bulk speeds and temperatures are generated using a previously developed method which applies Maxwellian fits to measurements of the protons' velocity distribution function. Spatial maps and probability‐density histograms comparing the proton parameters between the two time periods are presented. The temperatures perpendicular ( T ⊥ ) and parallel ( T ∥ ) to the background magnetic field are found to be 20%–35% lower during solar maximum. Though the overall distributions of the temperature ratio T ⊥ / T ∥ do not change, the regions with higher anisotropy ( T ⊥ / T ∥ > 1) are found farther downstream from the bow shock during solar maximum than minimum. This is consistent with the previously observed growth of mirror modes during solar maximum and their decay during minimum. Key Points: We compare proton bulk velocities and temperatures in the Venus plasma environment during solar minimum and maximum We measure lower perpendicular and parallel proton temperatures in Venus' magnetosheath during solar maximum than during solar minimum The spatial distribution of the temperature anisotropy is consistent with the observed growth and decay of mirror modes in the magnetosheath